Effects of Cyclization on Activity and Stability of α-Conotoxin TxIB - Li, Xincan (Mar Drugs, 2020)
α-Conotoxin TxIB specifically blocked α6/α3β2β3 acetylcholine receptors (nAChRs), and it could be a potential probe for studying addiction and other diseases related to α6/α3β2β3 nAChRs. However, as a peptide, TxIB may suffer from low stability, short half-life, and poor bioavailability. In this study, cyclization of TxIB was used to improve its stability. Four cyclic mutants of TxIB (cTxIB) were synthesized, and the inhibition of these analogues on α6/α3β2β3 nAChRs as well as their stability in human serum were measured. All cyclized analogues had similar activity compared to wild-type TxIB, which indicated that backbone cyclization of TxIB had no significant effect on its activity. Cyclization of TxIB with a seven-residue linker improved its stability significantly in human serum. Besides this, the results showed that cyclization maintained the activity of α-conotoxin TxIB, which is conducive to its future application.